Sequencing and characterization of leaf transcriptomes of six diploid Nicotiana species. Issue 1 (December 2016) - Long, Ni; Ren, Xueliang; Xiang, Zhidan; Wan, Wenting; Dong, Yang
Abstract Background Nicotiana belongs to the Solanaceae family that includes important crops such as tomato, potato, eggplant, and pepper.Nicotiana species are of worldwide economic importance and are important model plants for scientific research. Here we present the comparative analysis of the transcriptomes of six wild diploidNicotiana species. Wild relatives provide an excellent study system for the analysis of the genetic basis for various traits, especially disease resistance. Results Whole transcriptome sequencing (RNA-seq) was performed for leaves of six diploidNicotiana species, i.e.Nicotiana glauca, Nicotiana noctiflora, Nicotiana cordifolia, Nicotiana knightiana, Nicotiana setchellii andNicotiana tomentosiformis . For each species, 9.0–22.3 Gb high-quality clean data were generated, and 67, 073–182, 046 transcripts were assembled with lengths greater than 100 bp. Over 90 % of the ORFs in each species had significant similarity with proteins in the NCBI non-redundant protein sequence (NR) database. A total of 2491 homologs were identified and used to construct a phylogenetic tree from the respective transcriptomes inNicotiana. Bioinformatic analysis identified resistance gene analogs, major transcription factor families, and alkaloid transporter genes linked to plant defense. Conclusions This is the first report on the leaf transcriptomes of six wildNicotiana species by Illumina paired-end sequencing and de novo assembly without a reference genome. These sequence resources hopefully will provide an opportunity for identifying genes involved in plant defense and several important quality traits in wildNicotiana and will accelerate functional genomic studies and genetic improvement efforts ofNicotiana or other important Solanaceae crops in the future.